The impact of integrating emotion focused components into psychological therapy: A randomized controlled trial. Issue 2 (21st August 2022) - Caspar, Franz; Berger, Thomas; Holtforth, Martin grosse; Babl, Anna; Heer, Sara; Lin, Mu; Stähli, Annabarbara; Gomez Penedo, Juan Martin; Holstein, Dominique; Egenolf, Yvonne; Frischknecht, Eveline; Krieger, Tobias; et al.
Abstract: Objectives: This paper presents a randomized controlled trial on assimilative integration, which is aimed at integrating elements from other orientations within one approach to enrich its conceptual and practical repertoire. Elements from Emotion‐Focused Therapy (EFT) were integrated into a form of cognitive behavior therapy: Psychological Therapy (PT). In one treatment condition, EFT was added to PT (+EFT) with the intent to enhance therapists' working with emotions. In the other condition, concepts and interventions based on the socialpsychological self‐regulation approach were added to PT (+SR). Our assumption was that the +EFT would lead to greater and deeper change, particularly in the follow‐up assessments. Method: Patients ( n  = 104) with anxiety, depression, or adjustment disorders were randomized to the two conditions and treated by 38 therapists who self‐selected between the conditions. Primary outcome was symptom severity at 12‐month follow‐up; secondary outcomes included several measures such as interpersonal problems and quality of life. Variables were assessed at baseline, after 8 and 16 sessions, at posttreatment, and at 6‐ and 12‐month follow‐up. Results: Contrary to our hypothesis, no significant between‐group effects were found. Conclusion: The findings first suggest the difficulty of topping an already very effective approach to psychotherapy. Alternative interpretations were that the EFT training, while corresponding to regular practice in AI, was not sufficient to make a difference in outcome, or that while profiting from the enhancement of abilities for working with emotions, this was outbalanced by negative effects of difficulties related to the implementation of the new elements.